1989
DOI: 10.1901/jeab.1989.52-47
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Diazepam Administration: Effects on the Acquisition and Performance of Response Chains in Humans

Abstract: The effects of repeated diazepam administration (80 mg) were assessed across a 12-hr time course with humans responding under a two-component multiple schedule of repeated acquisition and performance of response sequences. Subjects resided in an inpatient clinical research ward for the duration of the study. In each component of the multiple schedule, subjects completed sequences of 10 responses in a predetermined order using three keys of a numeric keypad. In the acquisition component, a new response sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
2
3
0
1
Order By: Relevance
“…Estazolam and triazolam impaired learning, recall, and performance on the repeated acquisition procedure, digit entry and recall task, and DSST as a function of dose. These findings systematically replicate previous reports that used these measures to assess the behavioral effects of anxiolytichypnotic-sedative compounds including alprazolam (Bickel, Hughes, & Higgins, 1990;Evans, Troisi, & Griffiths, 1994;Mumford et al, 1995aMumford et al, , 1995b, abecarnil (Mumford et al, 1995a), diazepam (Bickel, Higgins, & Griffiths, 1989, Bickel et al, 1990Desjardins, Moerschbaecher, Thompson, & Thomas, 1982;Higgins, Bickel, O'Leary, & Yingling, 1987;Higgins & Stitzer, 1990), lorazepam (Roache & Griffiths, 1987;Rush et al, 1993a), pentobarbital (Kirk et al, 1990;Roache & Griffiths, 1985), temazepam (Rush et al, 1993b;Rush & Griffiths, 1996), triazolam (Bickel et al, 1990;Evans et al, 1990;Kirk et al, 1990;Rush et al, 1993aRush et al, , 1993bRush & Griffiths, 1996), secobarbital (Higgins & Stitzer, 1990), and zolpidem (Evans et al, 1990;Rush & Griffiths, 1996). Estazolam and triazolam also increased participant-rated strength of drug effect and observer-rated sedation, which is consistent with the profile of effects produced by anxiolytic-hypnotic-sedative drugs (e.g., Evans et al, 1990;Rush et al, 1993aRush et al, , 1993b This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussionsupporting
confidence: 87%
“…Estazolam and triazolam impaired learning, recall, and performance on the repeated acquisition procedure, digit entry and recall task, and DSST as a function of dose. These findings systematically replicate previous reports that used these measures to assess the behavioral effects of anxiolytichypnotic-sedative compounds including alprazolam (Bickel, Hughes, & Higgins, 1990;Evans, Troisi, & Griffiths, 1994;Mumford et al, 1995aMumford et al, , 1995b, abecarnil (Mumford et al, 1995a), diazepam (Bickel, Higgins, & Griffiths, 1989, Bickel et al, 1990Desjardins, Moerschbaecher, Thompson, & Thomas, 1982;Higgins, Bickel, O'Leary, & Yingling, 1987;Higgins & Stitzer, 1990), lorazepam (Roache & Griffiths, 1987;Rush et al, 1993a), pentobarbital (Kirk et al, 1990;Roache & Griffiths, 1985), temazepam (Rush et al, 1993b;Rush & Griffiths, 1996), triazolam (Bickel et al, 1990;Evans et al, 1990;Kirk et al, 1990;Rush et al, 1993aRush et al, , 1993bRush & Griffiths, 1996), secobarbital (Higgins & Stitzer, 1990), and zolpidem (Evans et al, 1990;Rush & Griffiths, 1996). Estazolam and triazolam also increased participant-rated strength of drug effect and observer-rated sedation, which is consistent with the profile of effects produced by anxiolytic-hypnotic-sedative drugs (e.g., Evans et al, 1990;Rush et al, 1993aRush et al, , 1993b This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussionsupporting
confidence: 87%
“…Subjects in the current study demonstrated consistent patterns of response sequence acquisition across sessions, as evidenced by decreases in the number of incorrect responses emitted over trials. These results are consistent with the results from a number of studies (e.g., Bickel, Higgins, & Griffiths, 1989;Higgins, Woodward, & Henningfield, 1989).…”
Section: Response Sequence Acquisitionsupporting
confidence: 93%
“…This baseline permits an assessment of drug effects on responding in transition (i.e., learning) contrasted with steady-state (i.e., performance) conditions. Drug effects often differ for these two conditions (e.g., Bickel, Higgins, & Griffiths, 1989;Desjardins, Moerschbaecher, Thompson, & Thomas, 1982;Higgins, Woodward, & Henningfield, 1989), and, thus, inclusion of both conditions provides for a more comprehensive characterization of the effects of this commonly used drug combination than either condition alone. In addition, in prior studies with humans the repeated-acquisition and performance procedure has been sensitive to the acute effects of cocaine and alcohol alone, which makes it an interesting baseline on which to study the effects of these drugs in combination (e.g., Fischman, 1984;Higgins, Bickel, O'Leary, & Yingling, 1987;Higgins, Bickel, et al, 1989 All subjects were recent but occasional users of cocaine.…”
mentioning
confidence: 99%